2013
DOI: 10.1111/jcpt.12119
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing for off-label use and unauthorized medicines in three paediatric wards in Finland, the status before and after the European Union Paediatric Regulation

Abstract: The prescribing for off-label use and unauthorized medicines was more prevalent in 2011 than in 2001. This indicates that the recent legislation has had only minor or no impact on the authorizing status of medicines commonly used in paediatric inpatients in specialized care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 28 publications
4
65
2
4
Order By: Relevance
“…On the other hand, other studies reported that the route of administration was the most common reason for off-labeled/unlicensed prescriptions,713 for example, buccal administration of sedatives and analgesics, and administration of drugs via enteral feeding tube. We believe that the differences between our study and previous reports regarding the reasons might be the differences in the route of administration in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other studies reported that the route of administration was the most common reason for off-labeled/unlicensed prescriptions,713 for example, buccal administration of sedatives and analgesics, and administration of drugs via enteral feeding tube. We believe that the differences between our study and previous reports regarding the reasons might be the differences in the route of administration in children.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the differences between our study and previous reports regarding the reasons might be the differences in the route of administration in children. For example, according to Lindell-Osuagwu et al,13 buccal administration of sedatives and analgesics was the primary reason for off-labeled/unlicensed prescriptions. In the centers we investigated, buccal or nasal administration of drugs in children were rare.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective and prospective studies have been conducted in the United Kingdom (UK) [35], France [6], the Netherlands [7], Germany [8, 9], Switzerland [10], Finland [11, 12], Croatia [13], Italy [14], Portugal [15], across Europe [16], United States (US) [17], Brazil [18], Ireland [19], Israel [20], Malaysia [21] and Australia [1, 22, 23] in various hospital settings that have included Emergency Department patients, outpatients or inpatients (general and medical wards and paediatric and neonatal intensive care units). Most of the studies have been conducted over a period of weeks or months.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lindell-Osuagwu et al compared offlabel and unlicensed prescription rates in several paediatric wards in a Finnish university hospital. They actually found that off-label use and unlicensed drug use was more prevalent in 2011 than in 2001 (87). Also, on the basis of 117,665 admissions over 1 year in a French paediatric hospital, Lajoinie et al concluded that young children are still commonly treated with unlicensed drugs (88).…”
Section: Paediatric Regulation: Progress and Future Perspectivesmentioning
confidence: 99%